BORON DESORPTION IN SOME CALCAREOUS SOILS OF NINEVEH GOVERNORATE / NORTH OF IRAQ - M. Al-Obaidi; A. kashmola (Mesopotamia Journal of Agriculture)
The investigation was conducted to study the behavior of boron desorption in three calcareous soils, classified as calciorthid. The experiment of boron sorption was conducted by using a different concentrations (0,0.5,1,2,4,6,8,10,20) mg B.L-1 (as boric acid) at 298ْ k while desorption experiment was conducted from adsorbed soils by using (0.01) M CaCl2 at (289 ْ k ) in order to study of boron hystersis. Langmuir model was used to describe capability of boron adsorption / desorption then the desorption index was calculated. Obtained results showed that boron adsorption energy was (0.843-0.069) L. mg -1 while boron desorption energy was ( 10.037-22.683) L. mg-1, while the boron desorption index was ( 1.32 - 3.66) for this reason the boron adsorption was not reversible.